Identificación y elaboración de productos turísticos del cantón Salcedo - Uvillus Cedeño, Adriana Nikol (2023)
The research project was made in the Salcedo canton corresponding to the Cotopaxi province, current]y Salcedo is known as a step city, since visitors only go to the site to the buy artisan products, such as traditional ice cream typical from place that implies, which people do not stay overnight in the territory. The first aim, it is to validate the tourist attractions inventory and develop tourism products from study site. Which it is effected the PDOT bibliographic review from Salcedo canton, it was got the information from tourist attractions registry provided by the territory GAD, and with the help from MINTUR 2017 inventory sheets, It was made a comparative matrix to achieve the cultural tourist attractions inventory validation, the results showed the 41 cultural attractions existence, what are mostly in a conservation state, which have been systematized into a database. In the second aim, it was designed a tourist product with a cultural topic, which understand the study site analysis, supply and demand, geographical location, political map with it got a tourist route creation, what emcomasses tourist attractions, gastronomy, leisure and developed recreation in the Salcedo canton, this was structured based on the Tourism Products Planning Manual from Perú. For the third aim, it was applied a Focus Group, by considering the key actors in the tourist area with the got information was made the FODA matrix, and MEFE, MEFI matrices to achieve assorted gastronomy fairs, they considers as an offensive and defensive strategy, which they consists of innovating the promotion proposals within the different media for the survival strategy, it was considered to increase the responsible staff efficiency, through training workshops and finally the adaptation strategy, whicb focused on the cultural tourist attractions maintenance and adequate use that are focused to the promotion and dissemination, which will be applied to the tourist product.